Presentation - Tello Gilardi, Janet (2022)
The Permanent Commission on Access to Justice for Persons in Conditions of Vulnerability and Justice in your Community of the Peruvian Judicial Branch is pleased to present the fourth issue of the journal Llapanchikpaq: Justice. In this edition we present articles related to the protection of children and adolescents, the approach to the various forms of violence that violate their human rights, and access to justice for persons with disabilities.